PEMANFAATAN BIJI ALPUKAT (Persea americana Mill.) UNTUK PEMBUATAN EDIBLE FILM - Ana ' Yudiandani; Raswen ' Efendi; Ahmad ' Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Avocado seed was found to have high starchs of content and yet it has not been optimally utilized. Therefore this research was aimed to utilized the starchs of avocado seed as material of edible film and to get the best formulations of addition of starchs avocado seed. This research was conducted experimentaly by used Complete Randomized Design (CRD) with five treatmens and three replications which followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatmens in this research include P1 (1,5 g starch avocado seed), P2 (2,0 g starch avocado seed), P3 (2,5 g starch avocado seed), P4 (3,0 g starch avocado seed) and P5 (3,5 g starch avocado seed). The results of variance analysis showed that addition of concentrations starchs avocado seed gave significantly affect on thickness, solubility, water uptake and water transfer edible film. The best formulations was obtained on the edible film with addition of starch avocado seed 3,5% which has thickness of 0,1053 mm, solubility of 22,31%, water uptake of 64,93%  and water transfer of 0,0402 g/hour.   Keywords: edible film, starch avocado seed